Nickel as A Strategic Mineral and Its Potential Resources in X-Field, North Konawe, Southeast Sulawesi, Indonesia - Fatimah, Dian Yesy; Her Krissanto, Juvens Yuda; Pamunga, M. Nur Alif; Nugroho, Rio P. (Geological Engineering Department Universitas Gadjah Mada, 2023)
Indonesia is the world's largest producer of Nickel laterite deposits. By the regulation of UU No. 3 2020, due to its utility as the main component of batteries on electric vehicles (EV), nickel is one of the metal minerals that play important role in energy transition issues. It will drive the increasing demand for Nickel and Indonesia needs a massive exploration and specific regulation, especially for this deposit. The focus of this research is to discuss how important Ni is as a strategic mineral and its potential resources in North Konawe, Southeast Sulawesi. The methods are based on field data analysis and references study.X-Field is located in Lasolo Island, North Konawe, Southeast Sulawesi. This area has potential resources of Ni-laterite deposit. The lithological condition consists of a massive ultramafic igneous rock complex. The host rock has already been enriched by the serpentinization process. The geochemical analysis shows various ranges of 0.87-2.43% Ni content from different soil zone. To this day, the government regulation of Ni in a specific way as a critical mineral is still not present. The lack of data transparency (supply chain) and policy synchronization urgently need to be solved.